Understanding Human Resource Outsourcing in Indian Context - Garg, Rashi (Journal of Commerce and Trade, 2019)
The Human Resource Outsourcing have emerged as a new trend in HR activities. Outsourcing has gained value in recent years in India as well as globally in providing the HR services. Most of the managers nowadays think that their employees are their most valuable asset and managing human resources is important and has also become a most critical role in organisations, uptill now all the Hr services were looked after by Hr departments making it very tiring , time consuming and costly for the organisations so they look Hr outsourcing as solution to all the problems and with the outsourcing it has relieved the burden of Hr professionals and also helped in retaining and developing of employees.. Hr professionals are now taking care of core activities and rest are outsourced and have also retained the employees by providing good services of payroll recruitment etc . In this paper we are discussing about HR outsourcing , the functions of HR outsourcing and the companies helping in Outsourcing the HR activities. The main aim of the paper is to focus on how Hr outsourcing activities or services are affecting Indian market and till what extent they have captured Indian market and which companies are functioning in India as Hr outsourcing companies. Classification-JEL : E 24, J 24, O 15.